Novel sound characterization of brackish water - Din, Jafri (Faculty of Electrical Engineering, 2009)
The objectives of this research are to formulate a novel characterization of underwater sound for brackish water for Sea bass (Cynoscion nobilis), to identify sound pollution sources affected conductive environment for Sea bass, to characterize aquaculture environment sound for brackish water, and to propose an underwater audio threshold level for fish aquaculture. The expected outcome is a method of improving Sea bass productivity and breeding using underwater audio. Breeding farm (pond) dimension is 25 x 100 m and 2 m depth. Total of 6 paddle wheels were used in the edge of the pond. Sound profile has been measured to investigate the relative amplitude at different location and depth. These sound pressure level has been measured by using Cetacean hydrophone C304 which the range frequency of 7 Hz to 250 kHz. Emphasis has been given on the frequency range between 10 and 50 Hz. SpectraPlus software has been used to perform the analysis. Two cages of 3 x 3 m were used in the edge and centre of the pond. The study involved monitoring the growth of 20 fish in the each cage and 15800 fish outside the cage. Sound profile has been measured for each cage. Spectrum frequency of sound profile has been analyzed. Chemical properties and water quality been monitored. The cage at the edge of the pond experienced higher sound profile. The size and weight of fish inside the cage is less than outside the cage. Fish in the cage shows linear growth, while fish outside the cage shows exponential growth. No significance effect on fish growth for both cages. Thus, it shows that sound doesnt affect the fish growth. Mobility of fish in the cage limits their movement, therefore it cause stress and difficulties to access the food.